Penegakan Hukum Terhadap Perempuan Dan Anak Sebagai Korban Kekerasan Seksual Perspektif Viktimologi - Karina Salsabilla (CV. ITTC INDONESIA, 2024)
the role of victimology in law enforcement related to the protection of women and children as victims of sexual violence. Using a normative legal research method, this study analyzes existing legal norms and practices in the field related to victim protection. Through a review of applicable laws and legal protection policies, this study identifies factors that influence the risk of victimization and the psychological impacts experienced by victims. The results of the study indicate that a deep understanding of victimology can create a more effective and responsive protection system to the needs of victims. The challenges faced, such as social stigma and limited access to services, require collaboration between the government, the community, and non-governmental organizations. In addition, this study emphasizes the importance of the Law on the Crime of Sexual Violence and holistic protection for victims, including legal assistance, rehabilitation, and recovery. To achieve justice, gender sensitivity is needed in the judicial process and training for law enforcement officers. This study recommends increasing public awareness of victims' rights and access to rehabilitation services, in order to ensure that protection and justice for victims of sexual violence can be realized effectively.